Analysis of Urban Infrastructure Carrying Capacity and User Satisfaction Level at the Medan–Deli Serdang Border - Muzakir Riza; Abdiyanto; Abdi Sugiarto (CV. Doki Course and Training, 2026)
The Medan–Deli Serdang border area plays a strategic role as a mobility corridor and a regional movement node that supports social and economic activities. The high intensity of movement and the complexity of activities in this area require adequate infrastructure and accessible public services to meet users’ needs. This study aims to examine the interrelationship between infrastructure capacity, service accessibility, and user satisfaction in the Medan–Deli Serdang border area. A descriptive research approach was employed by collecting primary data through questionnaires, field observations, and documentation, complemented by secondary data from official statistical publications and government reports. Quantitative and qualitative analyses were integrated to provide a comprehensive overview of existing conditions. The results indicate that both infrastructure capacity and service accessibility are generally perceived at a moderate level, while user satisfaction also tends to fall within the same category. A stronger interrelationship is observed between service accessibility and user satisfaction compared to the physical capacity of infrastructure. These findings suggest that ease of access, travel efficiency, and the quality of supporting services play a crucial role in shaping user experiences in border areas. The study is expected to contribute to more responsive planning and management of infrastructure and public services based on users’ perspectives